IMPROVEMENT OF MECHANISMS FOR FORMATION, DEVELOPMENT AND CHANGE OF POWERS OF INDUSTRIAL ENTERPRISES - Murodullayev Bahadir Murodullayevich (Journals Park Publishing, 2022)
The subject of the study is the formation, development and transformation of the competencies of high-tech enterprises that produce technically complex products, the identification of their new and meaningful characteristics, the assessment of the costs of updating the composition of competencies in order to increase innovation activity. The purpose of the study is to show various options for the composition of costs in the areas of development and transformation of the main - technical, technological, personnel, intellectual - competencies of the organization. Methods were used: graphical visualization for structuring information in directions and ways of developing the key components of competencies Since the main elements of the enterprise production system (material and human resources, equipment and technologies, organizational and managerial subsystem) serve as sources for the formation of competencies, their three basic components are: research and transformation competencies; systematization of existing scientific approaches to the development of competencies of high-tech enterprises. As a result of the study, various options for the composition of the costs for the development and transformation of the competencies of organizations engaged in the creation of technically complex innovative products were considered and evaluated in the areas of "acquisition" of competencies and on the main structural elements of the organization's competencies; the criteria for making a reasonable managerial decision on the direction of development of competencies were identified - by the organization's own resources or through the transition to distributed design and production of technically complex products; an algorithm for choosing the direction of formation and development of the organization's competencies is proposed, taking into account the proposed criteria; the conclusion is made about the economic feasibility of integrating the competencies of individual enterprises and organizing distributed design and production of innovative products.